2014
DOI: 10.1093/toxsci/kfu246
|View full text |Cite
|
Sign up to set email alerts
|

Species Extrapolation of Life-Stage Physiologically-Based Pharmacokinetic (PBPK) Models to Investigate the Developmental Toxicology of Ethanol Using In vitro to In vivo (IVIVE) Methods

Abstract: To provide useful alternatives to in vivo animal studies, in vitro assays for dose-response assessments of xenobiotic chemicals must use concentrations in media and target tissues that are within biologically-plausible limits. Determining these concentrations is a complex matter, which can be facilitated by applying physiologically-based pharmacokinetic (PBPK) models in an in vitro to in vivo extrapolation (IVIVE) paradigm. We used ethanol (EtOH), a ubiquitous chemical with defined metrics for in vivo and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…These BEC values are similar to those found in previous studies following binge-pattern oral administration of ethanol to developing mice (Jiang et al, 2007; Cui et al, 2010; Kane et al, 2011), rats (Maier et al, 1996; Ryan et al, 2008; Brocardo et al, 2012) and guinea pigs (Bailey et al, 2001; Iqbal et al, 2006; Olmstead et al, 2009), where neurocognitive and neurological teratogenic effects were observed. It should be noted that these BEC values are also similar to those predicted in a recent ethanol pharmacokinetic modeling study for pregnant mice after a single 4-g/kg oral dose of ethanol (Martin et al, 2015). However, the same study found these values to be approximately one-half of those predicted for pregnant humans after the same ethanol dose (Martin et al, 2015).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These BEC values are similar to those found in previous studies following binge-pattern oral administration of ethanol to developing mice (Jiang et al, 2007; Cui et al, 2010; Kane et al, 2011), rats (Maier et al, 1996; Ryan et al, 2008; Brocardo et al, 2012) and guinea pigs (Bailey et al, 2001; Iqbal et al, 2006; Olmstead et al, 2009), where neurocognitive and neurological teratogenic effects were observed. It should be noted that these BEC values are also similar to those predicted in a recent ethanol pharmacokinetic modeling study for pregnant mice after a single 4-g/kg oral dose of ethanol (Martin et al, 2015). However, the same study found these values to be approximately one-half of those predicted for pregnant humans after the same ethanol dose (Martin et al, 2015).…”
Section: Resultssupporting
confidence: 83%
“…It should be noted that these BEC values are also similar to those predicted in a recent ethanol pharmacokinetic modeling study for pregnant mice after a single 4-g/kg oral dose of ethanol (Martin et al, 2015). However, the same study found these values to be approximately one-half of those predicted for pregnant humans after the same ethanol dose (Martin et al, 2015). There was no effect of ethanol treatment on the amount of food consumed by dams or litters, although there was a small decrease in the amount of food consumed by dams of both groups on the first day of treatment only (data not shown).…”
Section: Resultssupporting
confidence: 83%
“…Calculated using interspecies and in vitro to in vivo extrapolation methods [45] Optimal human model [39] derived from the low-dose rat model Unsuccessful extrapolation…”
Section: Human Equivalent Dosesmentioning
confidence: 99%
“…This apparent decrease in oral uptake rate constant with age may simply reflect changes in the metabolic capacity of the GIT. In contrast, for ethanol, a nonlipophilic chemical with high water solubility, the apparent fitted oral uptake constant values remained the same until near weaning, at which time they increased slightly (Martin et al, 2015). This increase in first-order uptake rate constants near birth may be related to increases in paracellular transport in the intestinal epithelium.…”
Section: Enzymementioning
confidence: 86%